The genus Branchiosyllis Ehlers, 1887 from Philippines Islands, with the description of two new species - Álvarez-Campos, Patricia; San Martín, Guillermo; Aguado, M. Teresa (Zootaxa, 2012)
The species of Branchiosyllis from Philippines Islands, B. maculata, B. australis new comb. and B. exilis, have been re-viewed, with particular emphasis on the study of worldwide material of the latter. In addition, Branchiosyllis mayae andBranchiosyllis tagalog are described as new species. The former is characterized by its bidentate claw-shaped chaetae,unique in the genus, short dorsal cirri, and orange body with black stripes on prostomium (less pigmented), peristomiun,and anterior four to seven segments (more pigmented at bases of cirrophores). The latter is characterized by presence ofonly two claw-shaped chaetae per parapodium, ventral one larger than dorsal one, spindle-shaped tentacular cirri and dor-sal cirri with small pores and papillae, peristomium not visible dorsally and strongly dorsoventrally flattened body, pig-mented with dark central spot surrounded by two horizontal wide bands and faint coloured circles on each parapodia. A comparative table of all the species of the genus is also provided.